Experimental Validation of a Hierarchical Suspension Control via MR Damper. Issue 2 (2020) - Savaia, Gianluca; Corno, Matteo; Panzani, Giulio; Sinigaglia, Andrea; Savaresi, Sergio M.
Abstract: The suspension system has an important impact on vehicle dynamics, comfort and stability; these aspects are conflicting and the objective of an automatic control is to find a compromise. In this paper, the authors present an approach for the control of the vertical dynamics consisting of two layers: a low-level controller which fully exploits the properties of the magneto-rheological damper technology, and a high-level controller based upon a linearized skyhook for the full body control. The controller is experimentally validated on an actual vehicle in two road scenarios, which differ in their frequency excitation.